Simulasi Rancang Bangun Aplikasi Rumah Cerdas Berbasis Delphi - Achmat Yani; Achmad Ubaidillah (Universitas Darul Ulum, 2022)
Human life is growing rapidly from the residential environment to the industrial environment. One of the technological developments is the control system, so that everything is made easy and practical that can be monitored and controlled from the monitor layer or remotely. One example of the application of a control system in everyday life is a smart home that can regulate electronic equipment and monitor the condition of the house both wired and wirelessly. A smart home system is a combination of several systems between technology and services in a residential environment that serves to increase efficiency , security, and comfort for the occupants of the house. In general, a smart home system consists of several devices such as control, monitoring and automation of several electronic devices that can be accessed via a smartphone or computer layer. OFF can work. For the above experiment, it has worked well, temperature and humidity data can appear periodically and the ON/OFF button has also functioned properly to adjust the LED. If an error occurs in the simulation, it is expected to close the application via the task manager and recheck the program. for further research, if this is implemented in homes, the wiring can be tidied up so it doesn't fall apart. To connect from the application to the microcontroller please use USB TTL as serial communication.